The Edinburgh companion to literature and music - Sousa Correa, Delia da (Edinburgh companions to literature and the humanities., 2020)
This trailblazing companion charts and extends the work in this expanding interdisciplinary field and is an essential resource for researchers with an interest in literature and other media.